Design and Communication of Ecological Content on Sustainable Packaging in Young Consumers' Opinions. Issue 6 (17th August 2016) - Jerzyk, Ewa
ABSTRACT: Many companies today have noticed the growing sensitivity of consumers to social problems, reflected by their interest in environmental concerns (e.g., the use of sustainable packaging materials that are eco-friendly and safe for consumers and the environment). Producers seek, often based on intuition rather than knowledge, eco-arguments for their packaging to affect the perceptions of buyers and to influence their behavior. Creating an effective design and content for environmental messaging on sustainable packaging may be a significant element in building a competitive advantage for both product and brand. Therefore, the main objective of this article will be to answer the following questions: What content do consumers expect for ecological messages on packaging? Which attributes of sustainable packaging have a positive impact on consumer behavior? In what ways are consumers' purchasing intentions based on sustainable packaging? To answer these questions, the results of research conducted among Polish and French students will be presented.